Expanded Uses for the Nasolabial Flap - Weathers, William M.; Wolfswinkel, Erik M.; Nguyen, Huy; Thornton, James F. (Seminars in Plastic Surgery, 2013)
The nasolabial flap is an excellent choice for use in reconstruction of the nasal alar subunit due to its inherent properties that match skin tone and the convexity of the nose. Often overlooked as an option to use in nasal reconstruction, the nasolabial flap can be very advantageous. Indications for the nasolabial flap can be expanded to include reconstruction of the nasal tip, dorsum, soft triangle, and partial alar defects.
Keywords: nasolabial flap; nasal reconstruction; Mohs surgery